Potensi Kompres Dingin Terhadap Pencegahan Hematoma pada Pasien Pasca Percutaneous Coronary Intervention (PCI): Scoping Review - Aan Nuraeni; Almay Rayhan Arrafi; Aulia Rahmah; Epi Rohaeti; Finka Laili Nur Adzillah; Hilwah Nurul Arafah; Muhammad Iqbal Assafa; Rahayu Merdekawati; Rizkika Nur Amalia; Umy Riskyani; Vania Dwi Ramadhani; Firman Sugiharto; Etika Emaliyawati; Ristina Mirwanti (Malahayati Nursing Journal, 2023)
ABSTRACT Coronary Heart Disease (CHD) is a cardiovascular disease due to atherosclerosis or atherosclerotic occlusion of the coronary arteries. Various treatments can be done to treat CHD, including Percutaneous coronary intervention (PCI). The PCI procedure can cause complications. Hematoma is a significant complication that can cause swelling, pain, and increased discomfort. One of the many actions to reduce hematomas and pain is giving cold compresses. This study aimed to determine the potential of giving cold compresses to repair hematomas in post-PCI patients. This research uses scoping review method. Article searches were carried out on databases and search engines: PubMed, ProQuest, Google Scholar, and Garuda, in the period 2017-2022 with the keywords “Percutaneous Coronary Intervention” or “Cardiac Catheterization” and “Cold Therapy” or “Ice Application” and “Hematoma.”. There were seven articles included in the qualitative analysis. All articles discuss the effect of cold compresses on hematomas in post-PCI patients. Cold compresses help vasoconstrict blood vessels and speed up blood clotting time and formation. It was concluded that cold compresses could potentially prevent hematomas in post-PCI patients. Keywords: Cold compress, Cardiac Catheterization, Hematoma, Percutaneous Coronary Intervention (PCI)  ABSTRAK Penyakit Jantung Koroner (PJK) adalah penyakit kardiovaskular yang terjadi karena aterosklerosis atau oklusi aterosklerotik pada arteri koroner. Berbagai penanganan dapat dilakukan untuk mengatasi PJK, salah satunya adalah Percutaneous coronary intervention (PCI). Prosedur PCI dapat menimbulkan komplikasi. Hematoma adalah komplikasi utama yang dapat menyebabkan bengkak, nyeri, dan meningkatkan ketidaknyaman. Salah satu tindakan yang banyak dipilih untuk mengurangi hematoma dan nyeri yaitu dengan pemberian kompres dingin. Penelitian ini bertujuan untuk mengetahui potensi pemberian kompres dingin terhadap perbaikan hematoma pada pasien post PCI. Penelitian ini menggunakan metode scoping review. Pencarian artikel dilakukan pada database dan search engine: PubMed, ProQuest, Google Scholar, Garuda, dalam rentang waktu 2017-2022 dengan kata kunci “Percutaneous Coronary Intervention” or “Cardiac Catheterization” and “Cold Therapy” or “Ice Application” and “Hematoma”. Didapatkan 7 artikel yang masuk dalam analisa kualitatif. Sseluruh artikel berfokus membahas pengaruh kompres dingin terhadap hematoma pada pasien post PCI. Kompres dingin membantu vasokonstriksi pembuluh darah, mempercepat waktu pembekuan darah, dan pembentukan bekuan darah. Didapatkan simpulan bahwa kompres dingin memiliki potensi dalam mencegah terjadinya hematoma pada pasien post PCI. Kata Kunci: Kompres dingin, Kateterisasi Jantung, Hematoma, Percutaneous Coronary Intervention (PCI)